Investigation of Diarrhea in AIDS - Klaus E Mönkemüller; C Mel Wilcox (Canadian Journal of Gastroenterology)
Chronic diarrhea is a common problem in patients with acquired immune deficiency syndrome (AIDS), resulting in significant morbidity and potential mortality. In the early stages of immunodeficiency, human immunodeficiency virus (HIV)-infected patients are susceptible to infection with the same enteric pathogens that cause diarrhea in immunocompetent hosts, but with progressive immunodeficiency, these patients become susceptible to numerous opportunistic disorders. The main factor to consider when tailoring the work-up of diarrhea in the HIV-infected patient is the immune status, which is reflected by the total CD4 lymphocyte cell count. A CD4 count of less than 100 cells/µL is significantly correlated with opportunistic disorders. For the HIV-infected patient with diarrhea, repeated stool studies to investigate for bacteria, ova and parasites should be the first step. When either upper or lower gastrointestinal tract symptoms are present and stool studies are negative, endoscopy directed to the probable organ of involvement is appropriate. If localizing symptoms are absent, the most appropriate next test is sigmoidoscopy with biopsies. Not infrequently, despite extensive evaluation, the cause of diarrhea in patients with AIDS remains unexplained. Recently, the widespread use of highly active antiretroviral therapy, including protease inhibitors, has led to a change in the epidemiology of diarrhea in AIDS patients. As their immune status improves, HIV-infected patients treated with combination therapy become less prone to opportunistic disorders. However, diarrhea appears to be frequent because several antiretroviral agents can themselves cause diarrhea.